2020
DOI: 10.1021/acs.langmuir.0c02677
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Metal Ion-Mediated Adsorption of Spherical Nucleic Acids with a Large Hysteresis

Abstract: Spherical nucleic acids (SNA) refer to nanoparticles attached with a high density of oligonuleotides. Linear and spherical nucleic acids have many differences such as hybridization affinity, melting transition, and cellular uptake. In this work, these two types of DNA of the same sequence were compared for adsorption on polydopamine (PDA) nanoparticles and graphene oxide (GO). We focused on the effect of metal ions including Na + , Ca 2+ , and Zn 2+ since metal ions are indispensible for DNA adsorption on PDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…On the other hand, Gd 3+ and Zn 2+ showed the highest adsorption efficiency of 84 and 73% DNA, respectively. The higher DNA adsorption on PDA­(Gd 3+ ) was probably due to the stronger binding affinity between lanthanides and DNA, , as well as the higher affinity of PDA for Gd 3+ . , The general trend of the effectiveness of metal ions in the metal-doped NPs was similar to that on metal-adsorbed PDA NPs, where a higher DNA adsorption efficiency of lanthanides and transition metal ions was observed compared to Ca 2+ .…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…On the other hand, Gd 3+ and Zn 2+ showed the highest adsorption efficiency of 84 and 73% DNA, respectively. The higher DNA adsorption on PDA­(Gd 3+ ) was probably due to the stronger binding affinity between lanthanides and DNA, , as well as the higher affinity of PDA for Gd 3+ . , The general trend of the effectiveness of metal ions in the metal-doped NPs was similar to that on metal-adsorbed PDA NPs, where a higher DNA adsorption efficiency of lanthanides and transition metal ions was observed compared to Ca 2+ .…”
Section: Resultsmentioning
confidence: 80%
“…To quantify the concentration of leached Zn 2+ ions, 8-hydroxy-5-quinolinesulfonic acid (HQS) was used as a fluorescent probe, since Zn 2+ can induce its fluorescent emission at 521 nm (Figure A). , Using this standard curve, the Zn 2+ concentration in the supernatant of the 50 μg/mL PDA­(Zn 2+ ) was measured to be ∼0.7 μM (Figure A). Such a low concentration of free Zn 2+ ions was not expected to promote DNA adsorption. , …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…33 We previously showed that SNA can readily adsorb on PDA with a high affinity comparable to covalent linkages. 35,36 By closely packing SNA on PDA, a very high DNA density might be achieved. In this work, we designed a three-component hybrid material consisting of a Fe 3 O 4 core, a PDA shell, and a SNA decoration.…”
Section: ■ Introductionmentioning
confidence: 99%